Doskonalenie zarządzania wiedzą w przedsiębiorstwach województwa zachodniopomorskiego - Czerniachowicz, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Chosen issues referring to the realization of the concept were presented in the report of managing knowledge in companies of Zachodniopomorskie Province. The realization of the processes of knowledge management requires identification of available knowledge in the organization and/or in the environment and applying this knowledge to effective action. And so the attention was paid to utilizing knowledge and skills and chances to use computers during the realization of tasks by workers being in touch with customers, and influencing the image of the company. The concept of knowledge management includes also gaining new knowledge, creating new assets of knowledge. And therefore in the present study the number of reported and put into practice innovative projects was analysed, as well as the average economic effect ascribed to one applied inventive project. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 105-114